2021
DOI: 10.18502/acta.v59i8.7249
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Health Care for Afghan Refugees as a Minor Ethnicity in Iran; Clinical Differences and Racial Equality in Health

Abstract: The aim of this research was to look at the clinical differences between Afghan refugees and the Iranian community, as well as the evaluation of healthcare inequalities against Afghan refugees. ‎This was a 1:2 matched case-control study carried out at two tertiary hospitals of Jahrom city, southern Iran, from January 2020 to December 2020. Cases were COVID-19 infected Afghans, and controls were Iranian patients. Demographic data, Self-reported symptoms, disease history, and initial symptom to referral length w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…As their study population had different diseases, we can see how different these scoring systems can be in various medical conditions. There are many research studies performed in Jahrom city, in the same study setting as the current study, 15.54% of patients in a study were admitted to ICU (22) which was high as well as our study. This necessitates the proper risk stratification of patients at arrival in the emergency department to decrease the rate of ICU admissions and death.…”
Section: Discussionsupporting
confidence: 72%
“…As their study population had different diseases, we can see how different these scoring systems can be in various medical conditions. There are many research studies performed in Jahrom city, in the same study setting as the current study, 15.54% of patients in a study were admitted to ICU (22) which was high as well as our study. This necessitates the proper risk stratification of patients at arrival in the emergency department to decrease the rate of ICU admissions and death.…”
Section: Discussionsupporting
confidence: 72%
“…Previous clinical studies in the city have shown that gender differences were associated with their clinical status among those who died in COVID-19 and that the role of gender was also seen to some extent in this scrutiny. Several other studies have dealt with the status of laboratory factors of coronary patients [53][54] and the role of race [55] and even how pre-hospital and emergency systems [56] function in Jahrom city. These factors were not examined in the proposed study.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…Previous clinical studies in Jahrom have shown that gender differences were associated with their clinical status among those who died in COVID-19 and that the gender role was also seen to some extent in this investigation. Several other studies have dealt with the status of laboratory factors of coronary patients [53 and 54] and the role of race [55] and even the functioning of prehospital and emergency systems [56] in Jahrom city and it can be addressed in future studies. In another study in the Jahrom city itself, a high level of gastrointestinal symptoms was vivid, which was less seen in our study [57].…”
Section: Results and Disscusionmentioning
confidence: 99%
“…Further studies should be performed on the causes of various complications caused by COVID-19 to determine the exact relationship between the pathogenesis, prognosis, and severity of the disease. Our previous studies in Jahrom show that many other factors like paraclinical findings (22), gender (23), and ethnicity (24), or even method of referral to a medical center (25) might determine the outcome.…”
Section: Limitations Of the Studymentioning
confidence: 99%